Skin hydration is significantly increased by a cream formulated to mimic the skin’s own natural moisturizing systems - Spada F; Barnes TM; Greive KA (Dove Medical Press, 2018)
Fabrizio Spada, Tanya M Barnes, Kerryn A Greive Research and Development, Ego Pharmaceuticals Pty Ltd, Braeside, VIC, Australia Background: Moisturizers are topical products designed to improve and maintain the skin barrier function and to help prevent dry skin.Materials and methods: A new moisturizer (Ceramide cream) was formulated containing ingredients which mimic the skin’s own natural moisturizing systems. Corneometry was performed at baseline, 2, 4, 6 and 24 hours following a single application of Ceramide cream to healthy skin, and compared to three reference moisturizers available over-the-counter, and placebo. Transepidermal water loss (TEWL) was also measured following a single application of Ceramide cream compared to baseline, and its safety was assessed by repeat insult patch test, ophthalmologist and pediatric testing.Results: A single topical application of either the Ceramide cream or the three reference moisturizers resulted in a significant increase in skin hydration over time (P<0.001). The placebo cream did not significantly increase skin hydration at any time point. At 24 hours post-application, skin hydration measured for Ceramide cream was significantly greater (P<0.05) than that measured for all three of the reference moisturizers tested. Ceramide cream was also found to significantly decrease TEWL (P<0.001) over 24 hours, and was shown to be non-sensitizing to the skin of both adults and children and non-irritating to the skin, eyes and related eye area.Conclusion: Ceramide cream increases skin hydration and improves barrier function which may make it suitable for use on dry skin. Keywords: ceramide, moisturizer, stratum corneum, dry skin, humectant, emollient, occludent, transepidermal water loss, natural moisturizing factor